Enhancement of the security in LoRaWAN communication with post-quantum-cryptography - Figlarz, Gabriel Rossi (2025)
Long Range Wide Area Network (LoRaWAN) is the protocol that encodes information in radio waves and transmitting information through large distances. The cruciality of the information communicated awakens interest from malicious parties to acquire the communicated data via impersonating attacks or keys interception. Mitigating actions to ensure the security in LoRaWAN communication are under the threat of Quantum Computing (QC) advances. Post-quantum-cryprography (PQC) is composed by mathematically complex problems that quantum computers are not able to solve yet. Hence, PQC can ensure secure communication between IoT devices when quantum computers reach their full potential. Considering this, this work proposes an enhancement in LoRaWAN communication by implementing the PQC ML-KEM1024 algorithm in the protocol. An application was developed simulating LoRaWAN communication between a device and the whole circuit, considering a gateway, a network server and, an application server through a socket network. The assessed performance compared with benchmarks the time of execution and memory consumption at each step of the KEM algorithm. It was reached satisfactory level of results comparing to the references in bibliography and the methodology was validated. The results prove that PQC is fit for IoT communications and the enhancement in the security is feasible in many use cases. However, optimizations in the performance would expand the areas of usage of the proposed methodology.